PENGARUH MEDIA EDUKASI VIDEO ANIMASI TERHADAP PENGETAHUAN MASYARAKAT MENGENAI PENCEGAHAN HIPERTENSI DI KABUPATEN BANDUNG (Jurnal Kesehatan Siliwangi, 2023)
Background: According to WHO data, worldwide around 972 million people, or 26.4% of people worldwide suffer from hypertension, this figure is likely to increase to 29.2% in 2025. Hypertension is common and has a fairly high mortality rate. and affect a person's quality of life and productivity. West Java data on hypertension in Bandung Regency in 2019 as many as 192,787 patients and the Sangkanhurip Public Health Center contributed 19.49%. Purpose: To determine the effect of education through animated video media regarding the prevention of hypertension in the community in RW 05 Sangkanhurip Village, Bandung Regency. Methods: The research method used in this study was a quasi-experimental research design with one group pretest-posttest without control. With a sample of 78 respondents. Data analysis used the Wilcoxon test to prove the research hypothesis. Results: The average score of respondents' knowledge before being given animated video media was 61.15. The average knowledge score after being given animated video media is 78.08. The percentage increase in knowledge is 27.68%. The p-value on the knowledge of respondents before and after being given animated video media was (p = 0.000). The influence of animated video educational media on knowledge, because animated videos can explain in real terms, with visualization, the material described can be described. Conclusion: The influence of animated video educational media on public knowledge about hypertension prevention in RW 05 Sangkanhurip Village, Bandung Regency.